Assessment of reading comprehension, use of strategies and their relationship with academic and sociodemographic variables in university students - Guerra-García, Jorge (2021)
The aim of this research was to identify the levels of reading comprehension, the use of strategies and the motivation towards reading, and to relate them to different sociodemographic and academic variables, in students of the Biology career of the National Autonomous University of Mexico (UNAM), Campus Iztacala. Fifty-four students participated and were remotely applied the Instrument for Assessing Reading Comprehension in University Students, the Inventory of Metacognitive Strategies and Reading Motivation and a self-report to measure various academic and socio-demographic variables. The results showed a low level of reading comprehension, given that only 45% of the test was answered correctly; they reported a high use of strategies, -those related to reading analysis, identification of information and motivation towards reading general texts- and only statistically significant relationships were found in reading comprehension and parent's schooling (F(2-51)= 3,303, p= .045) and also with having access to text markers [t(52)= -2,155, p= .036] and Post it®  [t(52)= -2,466, p= .17]. It is concluded that these results, although they should be taken with caution, are evidence of comprehension and reading strategies in Biology students.